dy/dx=√(y-x) plz solve it
Answers
Answered by
13
Given that,
dy/dx = √(y - x) ...(i)
Let, y - x = z²
∴ dy/dx - 1 = 2z dz/dx
⇒ dy/dx = 1 + 2z dz/dx
From (i), we get
1 + 2z dz/dx = z
⇒ 2z dz/dx = z - 1
⇒ 2z/(z - 1) dz = dx
⇒ 2 (z - 1 + 1)/(z - 1) dz = dx
⇒ 2 dz + 2 dz/(z - 1) = dx
∴ integrating, we get
2 ∫ dz + 2 ∫ dz/(z - 1) = ∫ dx + c, where c is integral constant
⇒ 2z + 2 log(z - 1) = x + c
⇒ 2 √(y - x) + 2 log{√(y - x) - 1} = x + c,
which is the required solution.
#
Answered by
15
please see attached file
Attachments:
![](https://hi-static.z-dn.net/files/d35/96b3906ad9b625fcf0df012808173c5f.jpg)
Similar questions